1999
DOI: 10.1148/radiology.210.1.r99ja16217
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carcinoma: Can Dynamic Contrast-enhanced MR Imaging Help Predict Tumor Aggressiveness?

Abstract: Dynamic contrast-enhanced MR imaging does not facilitate differentiation between aggressive and nonaggressive tumors and therefore has no clinical role in assisting in treatment decisions in patients who are candidates for radical hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Several prior reports have shown correlations between DCE-MRI parameters and treatment outcome. (27, 29, 31, 3941)…”
Section: Discussionmentioning
confidence: 99%
“…Several prior reports have shown correlations between DCE-MRI parameters and treatment outcome. (27, 29, 31, 3941)…”
Section: Discussionmentioning
confidence: 99%
“…Most centers choose a primary surgical approach in low-stage (lower than IIb) cervical cancer patients [3]. Patients with involvement of the parametria (higher than IIa), or with a large tumor diameter (>4 cm), receive first-line radiation therapy in most institutes [2,3,11,12,13]. When correlated with surgical staging, clinical staging for primary cervical cancer has an error rate of 26-66% [6,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical carcinoma has intermediate signal intensity at T2-weighted images and is seen as a mass disrupting lowsignal-intensity fibrous cervical stroma [11]. Dynamic MR imaging technique after contrast injection has been reported to have no additional value in the tumor detection or evaluation of the extension of cervical carcinoma [11,12,16,17,18]. The cervical mass can demonstrate a wide variety of morphological features and may be exophytic, infiltrating, or endocervical [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy in the literature regarding the potential associations that may exist between histology and DCE-MRI findings in angiogenic-related pathologic processes. Whereas some studies have shown a positive correlation between tumor enhancement and microvascular density on histomorphometric assessment [30][31][32], other studies have shown no correlation [33][34][35]. Although we have used a semiquantitative scoring system rather than a histomorphometric procedure to quantify synovial vascularity, we postulate that microvascular density cannot be assumed to be the only determinant factor of tissue enhancement.…”
Section: Discussionmentioning
confidence: 87%